ANALISIS KINERJA KEUANGAN KOPERASI SIMPAN PINJAM - Dokman Marulitua Situmorang (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
How to see and know the financial performance of a cooperative, namely KSP Bhina Raharja Tegal Branch by viewing and analyzing its financial statements from 2016 to 2019 and estimating whether the cooperative has the potential to lose until it goes bankrupt? This is the purpose of this study using the Altman Z-Score method. The research method selected and used in this research is a descriptive type of research. The conclusion of this study was taken from the analysis carried out from the data of the cooperative's financial statements and based on the results obtained a conclusion about the condition of the financial performance of KSP Bhina Raharja Tegal Branch the authors can draw the following conclusions. The financial data generated based on the 2016-2019 financial statements, it can be concluded that the cooperative's financial performance is still in quite good condition but still needs more effective working capital management so that the profit generated can be maximized and can increase profitability ratios. Meanwhile, when viewed using the liquidity ratio, it can be said to be very good because the company has more current assets than its current liabilities. So that the company's short-term debt can be guaranteed using current assets owned by the company.While the prediction of bankruptcy based on the 2016- 2019 financial statements using the Altman Z-Score method shows the company is in a vulnerable area but the figures achieved almost exceed the point of not going bankrupt. Companies need to manage retained earnings more effectively in order to increase the Z-Score and bring the company to the point of not going bankrupt